The secrets we keep - Leaver, Trisha (Square Fish, 2016)
After the death of her twin sister Maddy, Ella decides to take on Maddy's identity in an effort to give her sister a kind of second chance at life. But while posing as Maddy, Ella realizes that her sister has been keeping some very dangerous secrets, and soon Ella is faced with the decision to reveal who she really is, or risk ending up just like Maddy.